Impact of cognition and psychoemotional status on falls in multiple sclerosis - Godelienė , R.; Sukockienė , E.; Danielius , V.; Stankunavičiūtė , V.; Mickevičienė , D. (Neurologijos seminarai, 2020)
Background. More than 50% of multiple sclerosis patients experience falls associated with accumulating disability, bladder dysfunction, and imbalance. However, impact of psychoemotional factors, including depression, anxiety, and cognition, on the risk of falling has not been studied in Lithuania so far. Data on the influence of psychoemotional factors on the falls are also controversial.Materials and methods. The study was carried out from April 2018 to January 2019 at the Hospital of Lithuanian University of Health Sciences, Neurology Department. Inclusion criteria: remission of relapsing-remitting multiple sclerosis, patients on disease-modifying treatment, EDSS score from 0 to 6.5, absence of mobility impairment due to other conditions, absence of psychiatric comorbidity. A self-reported questionnaire about falls in past 6 months was provided for the participants. Neurological examination, EDSS assessment, and symbol digit modality test (SDMT) were performed; anxiety and depression were rated using HAD scale, fatigue was rated using visual analog scale.Results. A total of 129 participants were enrolled in the study: 40 (31.0%) men and 89 (69.0%) women, mean age 43.6±11.1 years. Falls were experienced by 42 (32.6%) patients. There was no significant difference between fallers and non-fallers by gender (p=0.678). Mean age in fallers was 44.6±11.4 years, in non-fallers – 41.7±11.6 years, p=0.185. Disease duration in fallers was 115.55±74.9 months, and in non- fallers – 100.00±72.2 months (p=0.291). EDSS score was higher in patients who experienced falls than in those who did not (3.66±1.4; 2.31±1.2, p
Keywords: multiple sclerosis; falls; disability; anxiety; depression; cognition; fatigue